A252 IMPROVED QUALITY OF LIFE AFTER ENDOSCOPIC THERAPY FOR BARRETT'S ESOPHAGUS: A CANADIAN EXPERIENCE (2010–2016). (1st March 2018) - David, J; Belletrutti, P J; Gupta, M
Abstract: Background: Radiofrequency ablation (RFA) and endoscopic mucosal resection (EMR) are safe and effective modalities to eradicate Barrett's esophagus (BE). There is limited Canadian data as to the value of these endoscopic therapies particularly the impact on patient quality life (QoL). Aims: To determine the efficacy of RFA +/- EMR therapy for BE in the Calgary Zone including QoL impact. Methods: A retrospective review was completed of a prospectively maintained database of patients who underwent endoscopic therapy of BE in the Calgary Zone from June 2010-August 2016. Treatment response was evaluated primarily as complete remission of dysplasia (CRD =absence of dysplasia on 2nd surveillance endoscopy post-treatment) and complete remission of intestinal metaplasia (CRIM =absence of BE on 2nd surveillance endoscopy post-treatment). Since 2014, all patients who received endoscopic therapy were invited to complete QoL questionnaires at each visit. QoL responses from baseline and 9–15 months later were analysed. Results: Forty-two patients (95% male, mean age=67) with a mean BE length of 6.4cm completed endoscopic therapy. In those with high-grade dysplasia or intramucosal cancer (n=20), 18 had CRD (90%) and 15 achieved CRIM (75%) after a mean 3.2 RFA sessions (range 1–6). For low-grade dysplasia (n=15), 14 patients (93%) had CRD and 11 (73%) achieved CRIM after a mean 3.4 RFA sessions (range 1–8). In non-dysplastic BE (n=7), 6 (86%) achieved CRIM after a mean 4.7 RFA sessions (range 3–7). Overall, 15 (36%) patients had EMR during the course of treatment. Four patients (9%) developed a symptomatic stricture as a result of treatment. In the QoL survey (Table 1), after endoscopic treatment of BE, patients had significantly reduced worry about esophagectomy (p=0.01) and less stress due to their esophageal condition (p=0.03). There was also a trend toward decreased disease worry (p=0.14). Conclusions: In Calgary, endoscopic therapy was safe and highly effective in achieving CRD and CRIM. Impact of these treatments on QoL is also significant, as patients progressively had less worry about esophagectomy and associated stress. Further prospective data is needed to confirm this response is sustained. Funding Agencies: None